Efektivitas Kombinasi Buah Nanas Dan Rimpang Kencur Sebagai Alternatif Upaya Dalam Penurunan Tekanan Darah Penderita Hipertensi - Handayani, Sri; Enikmawati, Anik; Wjayanti, Wjayanti (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
Hypertension is a significant global health problem, with high prevalence in Indonesia, especially in Sukoharjo Regency. This study aims to evaluate the effectiveness of a combination of pineapple (Ananas comosus) and galangal rhizome (Kaempferia galanga) as a non-pharmacological alternative in lowering blood pressure in hypertension sufferers. Using a quasi-experimental one group pre-post test design, this study involved 24 respondents in Polokarto District, Sukoharjo Regency. The intervention consisted of giving boiled 10 grams of pineapple fruit and 5 grams of galangal rhizome in 200 ml of water, consumed three times a day for seven days. Blood pressure was measured before and after the intervention using a digital sphygmomanometer. Data analysis used the Paired Sample t-Test. The results showed a significant reduction in systolic (from 159.29 ± 12.31 mmHg to 145.67 ± 9.48 mmHg, p < 0.000) and diastolic (from 94.67 ± 11.52 mmHg to 84.71 ± 8.29 mmHg, p < 0.000) blood pressure. The effectiveness of this combination is associated with the bromelain content in pineapple which has anti-inflammatory and diuretic effects, as well as the potassium content and diuretic compounds in galangal. This research concludes that the combination of pineapple and galangal rhizome is effective in lowering blood pressure in hypertension sufferers, offering a potential natural alternative in hypertension management. However, further research is needed to explore the mechanism of action, optimal dosage, and long-term effectiveness of this combination in broader clinical use.